EVALUATING ALTERNATIVE PRODUCTION STRATEGIES FOR CLAMP SADDLE PRODUCTS TO IMPROVE PROFITABILITY: A CASE STUDY OF PT SENTRA PIPA NUSANTARA - Adityo Ramadhan; Gatot Yudoko (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The plastic piping industry depends on a complete portfolio of pipes and fittings to serve infrastructure, clean-water distribution, and industrial applications. PT Sentra Pipa Nusantara (a disguised name) completes part of its fitting portfolio through imported products, including the clamp saddle 63 mm × 1¼" that is currently purchased as a finished good under a third-party Malaysian brand. Although operationally simple, this import-based model limits the company’s control over product cost, brand ownership, and product design, and exposes profitability to supplier price, exchange-rate movement, and landed-cost components. At present the import model yields only about a 20% markup over cost (16.7% gross margin on the net selling price), and management has formally mandated a feasibility study to assess whether in-house production or contract manufacturing of an own-brand product could improve profitability. The study therefore addresses a clear managerial problem: under a constrained selling price, profitability improvement depends on the company’s ability to reduce unit cost and strengthen its sourcing strategy. This study compares three production-strategy alternatives, namely continuing to import, in-house production, and contract manufacturing (an indicative tolling or makloon scenario) and pursues three objectives: to compare the alternatives in terms of unit cost and unit margin against the net selling price; to test the sensitivity of each alternative to selected key cost drivers; and to recommend the most feasible strategy through a weighted multi-criteria feasibility assessment. The analysis proceeds in three connected stages. First, the unit cost of each alternative is built on a common per-acceptable-unit basis: import through a total landed-cost approach, in-house production through manufacturing-cost decomposition with units-of-production tooling allocation, and contract manufacturing through the indicative tolling scenario. Subsequently, the unit margin and margin ratio are then calculated against the actual net selling price. Second, a threshold sensitivity analysis varies five declared cost drivers (resin price, exchange rate, contract-manufacturing fee, reject rate, and tooling investment) one at a time to test the robustness of the ranking. Third, a weighted scoring matrix following the Simple Additive Weighting method integrates three quantitative criteria (comparative cost and margin, sensitivity robustness, and investment or MOQ commitment) and four qualitative criteria (implementation readiness, vendor dependency, market and customer acceptance, and intellectual-property consideration). Primary data were obtained through semi-structured interviews and internal consultations across the relevant functions, while the contract-manufacturing scenario and the reject rate were treated as validated planning assumptions; product quality was treated as a mandatory baseline and the recommendation as decision support rather than a final commercial decision. The results show that in-house production is the most economical and the most profitable route. It carries the lowest unit cost (Rp 19,208 per unit) and the widest unit margin (Rp 21,958, a 114.3% markup over cost), ahead of contract manufacturing (Rp 24,905; Rp 16,261; 65.3%) and import (Rp 34,305; Rp 6,861; 20.0%); both own-brand routes clear the 20% management target, whereas import only meets it at the threshold. This advantage is robust: across all eleven sensitivity scenarios in-house production remains the lowest-cost option and the ordering in-house < contract manufacturing < import is never reversed, with resin price the dominant driver for the own-brand routes and the exchange rate for import. In the weighted assessment, in-house production records the highest validated score (4.60 out of 5.0, against 2.72 for contract manufacturing and 2.46 for import) while staying within the Rp 300 million investment limit. The study therefore recommends a staged transition from import to in-house production of an own-brand clamp saddle, executed through a stage-gate roadmap and escalated to the CEO for the final go or no-go decision, with contract manufacturing retained as a fallback. The contribution of the study is a transparent and replicable evaluation framework — combining unit-cost build-up, threshold sensitivity, and a validated weighted scoring matrix — that can be applied to other imported fittings to support margin-improvement decisions.